THE REALITY VERSUS FICTION - ., Kustinah (MAGISTRA, 2016)
Fiction is a means of telling us something about reality (Iser,1987:53). This paper aims atpresenting a proof of that statement by analyzing a short story written by Melvin Dixon (1950-1992) entitledJesse. Iser said that every textual mode involves certain heuristic decisions; the model cannot be equated withthe literary itsef, but simply opens up a means of access to it. So, in the discussion, the writer of this paper willopen up a detailed interpretation through the text to give access for readers to find various point of view in aneffort to understand the story.Melvin Dixon is well known as an Afro-American writer who spoke and wrote about his homosexualityvery openly; for which he was both criticized and celebrated. The analysis of the short story will be a mentalevidence to convince readers the reality in fiction : through a short story, we see realities of life . Theoreticallyspeaking, the finding of this paper gives the application of trend in literary study : the term of past-present-future. We are learning a past writing, analyzes it at the present time, finding the values to understand the similartheme of Jesse in our real life and put those values for the enlightenment of our future. Literary works arealways written with a moral teaching inside.Key-words : The reality, fiction, speech-act theor